Deep ice as a geochemical reactor: Insights from iron speciation and mineralogy of dust in the Talos Dome ice core (East Antarctica) - Baccolo G.; Delmonte B.; Di Stefano E.; Cibin G.; Crotti I.; Frezzotti M.; Hampai D.; Iizuka Y.; Marcelli A.; Maggi V. (The Cryosphere, 2021)
Thanks to its insolubility, mineral dust is considered a stable proxy in polar ice cores. With this study we show that the Talos Dome ice core (TALDICE, Ross Sea sector of East Antarctica) displays evident and progressive signs of post-depositional processes affecting the mineral dust record below 1000g m deep. We apply a suite of established and cutting-edge techniques to investigate the properties of dust in TALDICE, ranging from concentration and grain size to elemental composition and Fe mineralogy. Results show that through acidic/oxidative weathering, the conditions of deep ice at Talos Dome promote the dissolution of specific minerals and the englacial formation of others, affecting primitive dust features. The expulsion of acidic atmospheric species from ice grains and their concentration in localized environments is likely the main process responsible for englacial reactions. Deep ice can be seen as a "geochemical reactor"capable of fostering complex reactions which involve both soluble and insoluble impurities. Fe-bearing minerals can efficiently help in exploring such transformations.